Effects of far infrared rays emitting clothing on recovery after an intense plyometric exercise bout applied to elite soccer players: A randomized double-blind placebo-controlled trial - Loturco, Irineu; Abad, C. C.C.; Nakamura, F. Y.; Ramos, S. P.; Kobal, R.; Gil, S.; Pereira, L. A.; Burini, F. H.P. [UNESP]; Roschel, H.; Ugrinowitsch, C.; Tricoli, V. (Index Copernicus, 2016)
The aim was to investigate the effects of far infrared (FIR) ray emitting clothes on indirect markers of exercise-induced muscle damage and physical performance recovery after a plyometric bout applied to soccer players. Twenty-one male players (18.9ï¿½0.6 years; 70.8ï¿½5.01 kg; 178.3ï¿½0.06 cm) performed 100 drop-jumps. Six hours after the bout, athletes put on FIR clothes (FIR) (density of 225 g ï¿½ m-2, 88% far infrared rays emitting polyamide 66 Emana yarn (PA66) fibre, 12% Spandex, emissivity of 0.88 and power emitted of 341 W/m2μm at 37ï¿½C in the 5-20 μm wavelength range, patent WO 2009/077834 A2) (N=10) or placebo clothes (PLA) (N=11). Mid-thigh circumferences, creatine kinase (CK), and delayed-onset muscle soreness (DOMS) were assessed before, immediately after and 24, 48, and 72 h after the bout. Squat (SJ) and countermovement jump (CMJ) heights were measured before and at 24, 48, and 72 h after, while 1RM leg press (maximum strength) was measured before and at 72 h after the plyometrics. No differences between groups were found in midthigh circumferences, SJ, CMJ or 1RM. CK increased significantly 24 h after the plyometrics in comparison to before (p<0.05) in both groups. PLA showed significant DOMS increases at 24, 48, and 72 h, while FIR showed significant increases at 24 and 48 h (p<0.05). DOMS effect sizes were greater in FIR (moderate at 48 h, ES=0.737 and large at 72 h, ES=0.844), suggesting that FIR clothes may reduce perceived DOMS after an intense plyometric session performed by soccer players.
Keywords: Delayed-onset muscle soreness\power; Football; Sports recovery